(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper is an attempt to study the miseries of women in Saadat Hassan Manto’s works, mainly including his short stories that are masterpiece of South Asian literature. This paper focuses on the issue of violence and miseries against women during the communal riots that followed the Partition of India in 1947. This paper is focused on gender-specific reading of partition genocide. It gives emphasis on various forms of violence imposed on women. These two stories “Open It” and “For Freedom” presents the lively picture of victimization and marginalization of women who suffered during the time of holocaust. In the aforesaid stories, Manto presents the true picture of marginalization, subordination and sufferings of women at the time of partition. In furthermore, the paper highlights the issue of abducted women. This study also adopts and adapts the ideas presented by Foucault to investigate the way that the female gender is marginalized and oppressed by a society rooted in a patriarchal setup. In this manner, women are further oppressed on the basis of not only being subjects but also on the basis of their gender. It is only through women that an ethnic community or nation-state demonstrates its sense of purity and honors. As a result, women turn into mute objects stripped of individual autonomy, of control over their bodies and lives. In this study, Saadat Hassan Manto’s short stories “Open It” and “For freedom” are analyzed thematically to investigate the ways in which women are subjugated, suppressed and raped during the time of holocaust.